A questão do humano e o animal rationale - Pivatto, Pergentino S. (Veritas (Porto Alegre), 2006)
A especificação de lógico e político no animal rationale serviu historicamente como determinativo da dimensão humana, e o humano resumiu-se no desenvolvimento destas faculdades. Esta interpretação é contestada no século XX por Scheler, Arendt e Levinas, entre outros, que repõem a questão da relação entre ser, natureza e humano. A problematização ontológico- naturalista leva a repensar a crença naturalista sobre a qual repousa o pensamento antropológico ocidental e desafia a ressignificar o humano a partir de novas compreensões, sobretudo a partir da alteridade. PALAVRAS-CHAVE – Animal rationale. Sentido do humano. Alteridade. ABSTRACT The specificity of the logical and the political in the animal rationale has historically served to determine its human dimension, as the human comes down to the development of these faculties. Such an interpretation has been questioned in the 20th century by Scheler, Arendt and Levinas, among others, who recast the question of the relation between being, nature and the human. The ontological-naturalist problematization leads us to rethink the naturalist belief on which lies Western anthropological thought, as it defies the signification of the human anew from the standpoint of new understandings, especially from alterity’s viewpoint. KEY WORDS – Animal rationale. Sense of human. Alterity.